IMPROVEMENT OF SHEAR STRENGTH PARAMETERS OF MODEL ORGANIC SOILS - Hameed Majeed, Adel; Shakir Al-Soud, Madhat; Hadi Sadiq, Zainab (Journal of Engineering and Sustainable Development, 2016)
The characteristics of organic soil are low permeability, low shear strength, and high compressibility, therefore organic soil has to be improved before any engineering works can commence. In this study, dry kaolinite is used as a clay mineral and fresh reed as an organic material for different percentages (0%, 2%, 5%, 8%, 12%, and 20%) by dry weight. Lime is used as a treatment material for different percentages (0%, 3%, 6%, and 9%) by dry weight. The experimental work includes a series of compaction and direct shear tests conducted on 48 samples. The effect of the addition of lime on shear strength parameters of non-decomposed and decomposed model organic soil was studied. The results showed that the cohesion values (c) increase with increasing organic content up to 5% for non-decomposed samples and up to 7.0% for decomposed samples while the angle of internal friction (φ) increases with the increase in organic content for both decomposed and non-decomposed samples. Also use of lime has increased the angle of internal friction of soil, especially when used within the range of (0-3) % lime content.